Faktor-faktor yang Mempengaruhi Speaking Performance Mahasiswa Jurusan Pendidikan Bahasa Inggris - Endang Setiyo Astuti; Indrawati Pusparini (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2019)
Speaking skill is one of the most important skill to be taught for English department students. Most activities in speaking class are oral presentations. However, there are many students admitted that they have obstacles in speaking performance. The main aim of this study was to find out the factors influencing students’ speaking performance in speaking class. Furthermore, it was also used to know the difficulties faced by the students of English department at IKIP Budi Utomo Malang. This study applied the descriptive qualitative method which describes the findings and the result of the study qualitatively. The data were collected by using observation, questionnaire, and documentation. This analysis found that both linguistics and non-linguistics aspects influenced students’ speaking performance. The linguistics aspect includes vocabulary, pronunciation, and grammar while the non-linguistic aspect covers confidence, anxiety, and topical knowledge.